CHARACTERIZATION OF INTERACTION IN BINARY MIXTURES BY DIELECTRIC ANALYSIS. - ARUNA P. MAHAROLKAR; A. MURUGKAR; S. S. PATIL; P. W. KHIRADE; S. S. PATIL (International Journal of Pharma and Bio Sciences, 2012)
The density (ρ), refractive index (nD), dielectric constant (es) and relaxation time (t) of binary mixture of Allyl Bromide (AB) with polar protic solvent 2-Butanol including those of the pure liquids, were measured over the complete composition range. The experimental data is used to calculate excess molar volumes (), excess dielectric constant (esE), excess inverse relaxation time (1/t)E, excess molar refraction (Rm)E, Bruggeman factor (fB). The variation of these parameters with composition and the effect of bonding in new chemical species were discussed from the point of view of intermolecular interactions in these mixtures. The decrease in excess molar volume () is attributed to the formation of hydrogen bonded associated species formed between unlike molecules.